TAADDÜDÜ'Z-ZEVCÂT VE AHKÂMUHU FI'L-ŞERÎ'ATI'L-ISLAMIY VE'L-KANÛNI'L-IRAKIYYI (DIRÂSEH MEWZÛ'IYYEH) - YABA, SAADALLAH AKRAM YABA (Fırat Üniveristesi, 2020)
Bu araştırma, İslam hukuku ve Irak hukuku ışığında çok eşlilik konusunu ele almaktadır. Çalışmamız üç bölümden teşekkül etmiştir: İlk bölüm, İslam hukuku ve Irak hukukunda evlilik konusunu ele alımıştır. Bu bölümde, aynı zamanda evlenmenin meşruiyetinden ve temel ilkelerinden bahsedilmiştir. İkinci bölümde, İslam öncesi dönemde ve İslam'da peygamberlerin ve çok eşliliğin çokluğundan bahsedildiği gibi, ilahi dinlerde çok eşliliğin yanı sıra, özellikle İslam'dan önceki uluslarda çok eşlilik konusu ele alınmıştır. Üçüncü bölüm, çok eşliliğin anlamı, meşruiyeti ve yönetimi ile çok eşliliğin nedenlerinden bahsedilmiştir. Aynı zamanda çok eşliliğin şartları ve genel ilkeleri hakkında bilgi verilmiştir. Son olarak çalışma, Irak Aile Hukuku başta olmak üzere bazı Arap ülkelerinin uygulamasında çok eşlilik konusu incelenmiş önemli gördüğümüz bulgulara ve önerilere yer verilmiştir. Anahtar kelimeler: Koca, Çok Eşlilik, İslam Hukuku, Irak Aile Hukuku

This research deals with the study of polygamy in light of Islamic law and Iraqi law. Its nature necessitated that it be divided into three parts: the first section talks about the meaning of marriage in Sharia and Iraqi law, it also talks about the legality and rule of marriage, and it talks about the wisdom of marriage and the types of marriage before Islam. The second section talks about polygamy in previous nations, especially before Islam, as well as polygamy in the divine religions "Jews and Christians," as well as it talks about the multiplicity of prophets and polygamy in the pre-Islamic era and in Islam. The third section deals with the meaning of polygamy, its legality and ruling, with mentioning the reasons for polygamy, and it also talks about conditions and controls for polygamy. Finally, the research deals with polygamy in the Iraqi Personal Status Law and the law of some Arab countries, and it mentions in the conclusion the most important findings and recommendations. Key words: Husband, polygamy, conditions, reasons, judgment, Islamic law, Iraqi law.
Polygamy and its provisions in Islamic and Iraqi law(Comparative study)
Keywords: Din